Game Edukasi Pengenalan Nama-Nama Sayuran Menggunakan Metode Development Life Cycle - Rizka Ramadhana; Fitri Rizani (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
This study aims to produce and test the feasibility of an educational game to recognize the names of vegetables for kindergarten children aged 4 to 6 years made using Construct 2 software. This game contains several games, namely guess pictures and arrange letters where the game is used as a learning medium for children. kindergarten level. The research method used is the Multimedia Development Life Cycle method that uses research stages (1) Concept, (2) Design, (3) Material Collection, (4) manufacture, (5) testing, (6) distribution. This study concludes that attractively designed interactive learning multimedia will generate motivation and stimulation for student learning activities, help students improve understanding of learning materials and foster learning creativity so that it will have an impact on improving the quality of learning. The results of this study are an application of the introduction of the names of vegetables that can help teachers in conveying material about learning the names of vegetables to students